2022
DOI: 10.1186/s12920-022-01197-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of CATSPER1, SPATA16 and TEX11 genes polymorphism with idiopathic azoospermia and oligospermia risk in Iranian population

Abstract: Background Male infertility is a heterogeneous disease which can occur due to spermatogenesis defects. The idiopathic azoospermia and oligospermia are the common cause of male infertility with unknown underlying molecular mechanisms. The aim of this study was to investigate association of idiopathic azoospermia and oligospermia with single-nucleotide polymorphisms of CATSPER1, SPATA16 and TEX11 genes in Iranian-Azeri men. Methods In this case–cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Min Xu et al found that Spata16 mRNA expression levels were 30-fold higher in human adult testes than in fetal testes, and they speculated that SPATA16 may be involved in spermatogenesis through its role in the Golgi apparatus [ 89 ]. Subsequent studies have confirmed that Spata16 is closely associated with acrosome formation and that its pathogenic mutations can cause globozoospermia and male infertility [ 90 , 91 , 92 ].…”
Section: Crispr/cas9: An In-depth Exploration Of Functional Genes For...mentioning
confidence: 99%
“…Min Xu et al found that Spata16 mRNA expression levels were 30-fold higher in human adult testes than in fetal testes, and they speculated that SPATA16 may be involved in spermatogenesis through its role in the Golgi apparatus [ 89 ]. Subsequent studies have confirmed that Spata16 is closely associated with acrosome formation and that its pathogenic mutations can cause globozoospermia and male infertility [ 90 , 91 , 92 ].…”
Section: Crispr/cas9: An In-depth Exploration Of Functional Genes For...mentioning
confidence: 99%
“…However, this class of genes is by definition understudied in model systems, and despite extensive efforts, there are no in vitro systems that accurately model spermatogenesis beyond the spermatogonial stem cell stage [17] . Genome-wide association studies (GWAS) and exome sequencing studies have revealed several genes associated with spermatogenic defects in infertile patients, but even the best hits from these studies explain only a small fraction of cases (reviewed in Cannarella et al , 2019) [3] , [18] , [19] . A major conclusion from genetic studies of patients with spermatogenic defects is that male infertility is associated with many de novo variants in diverse genes, making it difficult to achieve the power required to comprehensively identify genes that make critical contributions to male factor infertility [11] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a specific polymorphism in CAT-SPER1 gene (rs2845570) and SPATA16 gene (rs1515442) has a significant impact on the development of idiopathic oligospermia and azoospermia. 16 Multiple studies have reported the reduced expression of miR-34b/c and miR-499 in testicular or seminal tissues of patients with ologospermia. This is the justification for the potential association between miR-34b/c and miR-499 genes and human infertility conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Oligospermia and azoospermia are prevalent causes of male infertility, but their underlying molecular mechanisms and causes remain unexplored. The presence of a specific polymorphism in CATSPER1 gene (rs2845570) and SPATA16 gene (rs1515442) has a significant impact on the development of idiopathic oligospermia and azoospermia 16 . Multiple studies have reported the reduced expression of miR‐34b/c and miR‐499 in testicular or seminal tissues of patients with ologospermia.…”
Section: Introductionmentioning
confidence: 99%